An Accent-Based Approach to Automatic Rendering of Piano Performance: Preliminary Auditory Evaluation - BISESI, Erica; PARNCUTT, Richard (Archives of Acoustics, 2011)
We are exploring the relationship between accents and expression in piano performance.Accents are local events that attract a listener’s attention and are eitherevident from the score (immanent) or added by the performer (performed). Immanentaccents are associated with grouping (phrasing), metre, melody and harmony.In piano music, performed accents involve changes in timing, dynamics, articulation,and pedalling; they vary in amplitude, form, and duration. We analyzed thefirst eight bars of Chopin Prelude op. 28 n. 6. In a separate study, music theoristshad marked grouping, melodic and harmonic accents on the score and estimated theimportance (salience) of each. Here, we mathematically modeled timing and dynamicsin the prelude in two ways using Director Musices (DM) – a software packagefor automatic rendering of expressive performance. The first rendering focused onphrasing following existing and tested procedures in DM. The second focused on accents– timing and dynamics in the vicinity of the accents identified by the theorists.In an informal listening test, 10 out of 12 participants (5 of 6 musicians and 5 of6 non-musicians) preferred the accent-based formulation, and several stated that ithad more variation of timing and dynamics from one phrase to the next.